1999
DOI: 10.1038/sj.bmt.1702015
|View full text |Cite
|
Sign up to set email alerts
|

The number of nucleated cells reflects the hematopoietic content of umbilical cord blood for transplantation

Abstract: Summary:A single umbilical cord blood (UCB) collection may contain sufficient hematopoietic stem cells to achieve engraftment and repopulation of the hematopoietic system of children and adults after myeloablative therapy. The hematopoietic potential of a UCB unit is often defined by the number of CD34 + cells or the number of colony-forming units as measured in semisolid hematopoietic progenitor cell (HPC) cultures. However, these assays are relatively difficult to standardize between UCB banks. The number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
25
1
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 18 publications
4
25
1
2
Order By: Relevance
“…The presence of haemorrhage in the maternal and fetal areas of delivered placenta and the clots formed in fetal placental vessels could explain the loss of haematopoietic progenitor cells in ex utero collections. In our cases, total nucleated cells correlate with both CFUs and the number of CD34+ cells, indicating the TNC reflects haematopoietic content of CB units as shown by Lim et al 14 Besides, a smaller number of CB units was discarded for banking compared to ex utero vaginal and caesarean deliveries, and the only five cases with macroscopic clots belonged to the ex utero collection group. Time from cord clamping to collection also could contribute to differences between in utero and ex utero methods; while in the first case collection is performed immediately after CB clamping, in the second case it is necessary to wait until placental expulsion.…”
Section: Discussionsupporting
confidence: 76%
“…The presence of haemorrhage in the maternal and fetal areas of delivered placenta and the clots formed in fetal placental vessels could explain the loss of haematopoietic progenitor cells in ex utero collections. In our cases, total nucleated cells correlate with both CFUs and the number of CD34+ cells, indicating the TNC reflects haematopoietic content of CB units as shown by Lim et al 14 Besides, a smaller number of CB units was discarded for banking compared to ex utero vaginal and caesarean deliveries, and the only five cases with macroscopic clots belonged to the ex utero collection group. Time from cord clamping to collection also could contribute to differences between in utero and ex utero methods; while in the first case collection is performed immediately after CB clamping, in the second case it is necessary to wait until placental expulsion.…”
Section: Discussionsupporting
confidence: 76%
“…Recently, the statistics of accumulated clinical data confirmed that the number of nucleated cells/kg and therefore the number of stem and progenitor cells infused into the recipient was the most important factor influencing the probability and speed of engraftment. [3][4][5] It is thus critical that all efforts be made to ensure a large cell dose in the CB unit sufficient for a rapid and sustained engraftment.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the statistics of accumulated clinical data confirmed that the number of nucleated cells/kg and therefore the number of stem and progenitor cells infused into the recipient was the most important factor influencing the probability and speed of engraftment. [3][4][5] It is thus critical that all efforts be made to ensure a large cell dose in the CB unit sufficient for a rapid and sustained engraftment.In order to maximise the cell quantity in a single unit of CB, various studies have been carried out for their collection, processing and cryopreservation. Broxmeyer et al 6 described a two-phase method by which CB was firstly collected from the severed cord during placental delivery and then additional CB was obtained from multiple needle aspirations from the umbilical vein.…”
mentioning
confidence: 99%
“…Estudos estabeleceram a presença de CTH no sangue do cordão umbilical humano (BROXMEYER et al, 1989;GLUCKMAN et al, 1989;BROXMEYER et al, 1992;WAGNER et al, 1992;LIM et al, 1999), que apresentam habilidade de auto-renovação e diferenciação adequadas à reconstituição hematopoética (HERZOG et al, 2003) e são importantes na terapia celular e gênica. Além disso, em recente estudo foi relatada a presença de células-tronco mesenquimais multipotentes no cordão umbilical humano, as quais são capazes de originar diferentes linhagens celulares, demonstrando a capacidade progenitora do cordão umbilical (SECCO et al, 2008).…”
Section: Discussionunclassified